Strategi Bauran Pemasaran Jasa Pendidikan dalam Meningkatkan Minat Murid Baru di MAN 1 Tangerang dan MAN 5 Tangerang - Puji Ambarwati; Machdum Bachtiar (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Educational institutions in Indonesia are facing increasingly intense competition, requiring madrasahs to strengthen their marketing strategies to attract new students. This study aims to analyze the implementation of the educational service marketing mix strategy and its influence on student enrollment interest at MAN 1 Tangerang and MAN 5 Tangerang. The research employed a qualitative descriptive method through interviews, observations, and documentation involving school principals, teachers, and admission committees. The findings show that both schools have applied the seven elements of the marketing mix (product, price, place, promotion, people, process, and physical evidence) effectively, although their emphases differ. Product quality, competent teachers, and promotional activities through competitions and social media play significant roles in shaping a positive image and attracting new students. Meanwhile, the elements of place and price have a relatively minor impact but remain supportive. Overall, the integration of all seven elements creates a synergistic marketing strategy that enhances competitiveness and maintains a high level of new student interest. The results are expected to provide practical insights for improving educational marketing management in Islamic schools.